Becoming a father, staying a father: An examination of the cumulative fatherhood wage premium to U.S. residential fathers - GOWEN, Ohjae (Institutional Knowledge at Singapore Management University, 2023)
The instability of fathers’ co-residence with children has become an increasingly prevalent experience for U.S. families. Despite long-standing scholarship examining the relationship between fatherhood and wage advantages, few studies have investigated how variation in fathers’ stable co-residence with a child may produce temporal changes in the wage premium over the life course. Building on prior explanations of the fatherhood wage premium, I test if the wage premium grows with time since the birth of a resident child and if the premium depends on fathers’ co-residence with a child. I use marginal structural models with repeated outcome measures and data from 4060 men in the National Longitudinal Survey of Youth 1979 to assess the cumulative influence of co-residential biological fatherhood on wages. I find that each year of residential fatherhood is associated with a wage gain of 1.2 percent, while the immediate wage benefit to residential fatherhood is minor. Thus, the fatherhood premium is better understood as an unfolding process of cumulative advantage rather than a one-time bonus. Furthermore, the wage premium ceases to accumulate once fathers lose co-residential status with a child, which highlights the contingency of the premium on stable co-residence. Together, these findings shed light on one pathway through which family (in)stability—a phenomenon fundamentally embedded in individual life experiences—stratifies men’s wages across the life course.